Revitalization of coffee farms through rural tourism: case of Coatepec, Veracruz - Apodaca-González, Claudia; Juárez-Sánchez, José Pedro; Ramírez-Valverde, Benito; Figueroa Sterquel, Rodrigo (Revista Mexicana de Ciencias Agrícolas, 2018)
The neoliberal economic model and the liberalization trade of coffee brought lags in activity, displacement of domestic production that caused the closure of uncompetitive fields in the global market and social conflicts such as poverty and migration. Considering this, options such as social welfare programs and nonfarm rural employment (RNFE) including rural tourism were promoted. The research was conducted in Coatepec, Veracruz, coffee producer and declared “magical town”. The aim of the research was to analyse the possibilities of incorporating coffee producers in agro-tourism activities to diversify their income. A survey was administered to 72 coffee producers. The results showed that, the municipality coffee farmers have low education, elderly, and low coffee yields. Over 50% would like to offer agro-tourism services in pruning, fertilizing, planting, harvesting and hiking. They also need support and infrastructure for the implementation of tourism projects. We concluded that, low yields, lack of government support and low profitability affect the ability of the producers for participating in tourism to supplement their coffee activities.
Keywords: alternative tourism; coffee production; rural crisis; rural nonfarm employment